Benefits of flour storage as related to process efficiencies in milling - Johnson, Brent S. (Kansas State University, 2012)
The milling of wheat into white flour is a high volume, low margin business. Flour is a commodity. Competition is fierce. Over the past several years, there have been several mergers and acquisitions leading to fewer, but larger flour mills. The number of companies in the flour milling business has diminished as well. Flour sold in small packages on the grocery store shelf is but a small part of the business these days. Most flour is sold to commercial bakers in large bags or bulk trucks. The process of milling wheat into white flour consists of numerous variables within an extensive collection of equipment. It is the job of the miller to minimize the negative impact of these variables or at least hold constant as many of these variables as possible while achieving the best efficiency possible. To lessen the effect of these numerous variables on a large extensive system makes for a well running operation. When efficiency is achieved, a flour milling operation can be a profitable venture. A number of the variables that influence efficiency are affected by the amount of flour storage that a flour mill has. This thesis examines the benefits of flour storage as related to flour process efficiencies in milling. With flour mills operating at large output capacities, it is necessary for a flour mill to have adequate bulk flour storage bins as well as the right amount of warehouse space. Changes from one type flour to another in a flour mill require some time and an abundance of intervention by a skilled operator or miller. Having the proper amount of storage space makes it possible to minimize changes as well as the opportunity to optimize production of each specific flour type that is processed on the mill. To justify capital project money to invest in the proper amount of storage can be a challenge. Warehouse space and bulk flour storage can be expensive, and it is difficult to quantify how theoretical improvements will increase production and quality in the end product of flour. Using regression methods, production data obtained from an average sized commercial flour mill was used to estimate the increase in extraction due to a longer length of run allowed by the addition of storage space. By increasing the time a mill stays on a specific wheat mix to a minimum of twenty hours, there is a theoretical increase in extraction of 1.02 percentage points, resulting in wheat savings of over $500,000 per year. This resulting savings on the raw input material showed that capital expenditures on storage can be justified. A positive net present value and good internal rate of return show that the increased efficiency due to longer lengths of run justified the additional expense of the additional storage capacity. As volatility and the price per bushel of grain continue to increase, having the proper plant infrastructure with regard to storage space is of the utmost importance. Other benefits of storage will be realized as well in the area of flour quality and customer service.
Keywords: Milling science; Grain science; Extraction efficiency; Flour milling; Flour Storage; Economic analysis of storage; Agriculture, General (0473); Food Science (0359)